(untitled) (Annals of Medical Research, 2024)
Aim: This study examines workers’ health status and occupational risks in the automotive manufacturing and wood manufacturing sectors based on medical examinations conducted between January 2019 and January 2020. Materials and Methods: It involves 27 individuals with an average age of 36.26. Younger workers, especially those aged 20 to 35, show a higher propensity for workplace accidents due to their engagement in hazardous tasks and limited experience. The research emphasizes prevalent health issues such as metabolic syndrome, diabetes, obesity, and cardiovascular diseases among these workers, influenced by sedentary work routines and inadequate physical activity. Workers employed for 1-10 years exhibit the highest incidence of workplace accidents, warranting careful monitoring in this demographic. Key factors observed include tobacco consumption, blood cell counts, hemoglobin, glucose, liver function indicators, and exposure to hazardous substances. The study highlights prevalent hearing impairment and lung abnormalities in these workers, aligning with global trends in occupational health. Results: Our study recommends regular health screenings, lung film examinations during initial employment, and periodic check-ups for early detection and treatment. While acknowledging limitations, such as study specificity and resource constraints, it underscores the role of such studies in shaping policies, guiding preventive measures, and enhancing worker health and safety in high-risk industries. Conclusion: This study underscores the need for proactive health monitoring and regular screenings to safeguard workers’ health, even in industries where symptoms might not be evident.